Oral Manifestations in Acute Leukemia as the First Sign; The Interdisciplinary Approach of Diagnosis and Treatment - Paunica Stana; Giurgiu Marina; Dumitriu Anca (Journal of Mind and Medical Sciences)
Systemic diseases often present associated oral signs and symptoms, which can occur either from the beginning of the disease or during its evolution. In some cases the oral manifestations reveal an undetected and severe disease, like leukemia. According to the encountered oral signs and symptoms and their response to topical/ dental treatment, the dentist and physician should take into account specific additional tests, which could highlight a possible associated systemic disease. The most frequent oral manifestations associated with leukemia are represented by paleness of oral mucosa/ local abnormal colour of the gum, gingival petechiae, ecchymosis, bleeding associating painless gingival hyperplasia, hemorrhages, ulcerative necrotic lesions and buccal infections. We presented in this paper the relevant literature data in respect to the oral manifestations encountered in leukemia, exemplified with two suggestive cases. As a conclusion, dentists should be advised not only to recognize and treat the encountered oral lesions but also to refer the patient to specialized professionals for additional investigations, especially in the situation when suspect a severe systemic disease that require a precocious diagnosis or in the case when the establishment of diagnosis exceed the possibilities of the usual tests. Chemotherapy administration in association with topical/ oral solutions often leads to total or partial remission of the oral signs and symptoms.